Effect of hydrogen-producing magnesium-incorporated edible coating on Metabolomic and Volatilomic of beef meatballs - Kavrut, Enes; Bulut, Menekse; Celebi, Yasemin; Tekin, Ali; Cetintas, Yunus; Hayaloglu, Ali Adnan; Alwazeer, Duried (Elsevier Sci Ltd, 2025)
Meat products are highly perishable and have a short shelf life. The effects of using a molecular hydrogen- producing magnesium-incorporated coating (H2-P-Mg) on the color, pHysicochemical properties, deterioration, biogenic amines, free amino acid profile, and volatilomic profile of beef meatballs were evaluated. The meatballs were coated with different films as follows: group A (uncoated), group B (whey protein coating), group C (whey protein coating +7 % thyme extract), group D (whey protein coating +7 % thyme extract + Mg), and group E (whey protein coating + Mg). At the end of storage, group E samples showed higher color scores and lower pH (5.89) and Eh7 (+260 mV) values. At the end of storage, the H2-P-Mg coating (groups D and E) showed an inhibitory effect on TBARS (58-64 %) and biogenic amines (15.38-25.87 %). The concentrations of putrescine, histamine, cadaverine, and tyramine were reduced by about 15, 20, 22, and 26 % in Mg-coated samples compared to the control. Group E showed higher levels of histidine, tyrosine, and lysine. Group D had the lowest levels of ketones and aldehydes. The use of H2-P-Mg as an edible coating can bring numerous nutritional, safety, and technological benefits to meat technology.
Keywords: Beef meatball; Edible coating; Magnesium; Molecular hydrogen; Biogenic amines; Volatile profile